Chapter 5.38 The Development of the RMA Profession in Catalonia (Spain) - Cristina Borras; Aïda Díaz (Emerald Publishing Limited, 2023)
This chapter builds the historical overview of RMA in Catalonia and explores the detail of how research management and administration (RMA) has evolved, particularly in this northeast region, in Spain. It shows the specific conditions under which RMAs have become a community over time. This chapter includes major government support initiatives, and takes a closer look at the RMA's profiles, information on the evolution of their role, the possibilities for professional development, and their recognition. The results come from an open consultation carried out by AGAUR, the executive funding agency of the Government of Catalonia, addressed to RMAs of Research and Innovation (R&I) in Catalonia and published in a report in 2020. This is the second analysis carried out on the research management profession, and its recognition as a key player in attracting and managing competitive European (EU) and international funds.
10.1108/978-1-80382-701-820231072; 10.1108/978-1-80382-701-820231072; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262